Joseph Conrad and Popular Culture - Donovan, S. author. aut Link
XIII, 236 p.
Keywords: This highly original study opens up a new dimension to Joseph Conrad by revealing his lifelong fascination with the popular culture of his day. Drawing on original archival materials and treating subjects as diverse as Bovril advertising, spirit photography, sea shanties, global tourism, and the new sport of speed-walking, it shows how Conrad's fiction makes a sustained response to early-twentieth-century popular culture and will be of interest to all students, scholars and enthusiasts of Conrad.